(untitled) (Swiss Medical Weekly, 2019)
AIMS A new generation of physicians, millennials (also known as Generation Y), are entering residency programmes in internal medicine, and these young men and women learn and work in ways that are different from those of past generations. The aim of the present study was to investigate aspects contributing to the attractiveness to young residents of a career in general internal medicine (GIM) compared with medical subspecialties (SUB). METHODS In a cross-sectional online survey, we included residents working in residency facilities in GIM in German-speaking Switzerland. A total of 1818 junior residents were eligible. We looked for personal preferences, characteristics, and criteria influencing the choice of a career in GIM or SUB. RESULTS 392 out of 1818 (22%) residents participated in the survey (66% females); they had been in clinical training for 35.5 months on average. 87% of the respondents aspired to a title in GIM, and 29% of these to a SUB title as well. 71% of the women chose GIM and not a SUB vs 58% of the men (p <0.019). GIM residents gave significantly higher ratings to “broad range of expertise,” “flexible work hours” (p = 0.007), “work-life balance”, and “reconciliation of work, family and private life” than residents aiming at a SUB. SUB residents evaluated career-related criteria as significantly more important (p <0.0001). With regard to career motivation, GIM residents and female residents rated extraprofessional concerns significantly higher than SUB residents did (p = 0.019). In contrast, SUB residents showed significantly higher intrinsic motivation than GIM residents (p = 0.025). Only 28.2% of GIM residents had a mentor, compared to 49.6% of SUB residents (p <0.0005). Concerning personal perceptions of the future within the next 5 years, GIM residents attached significantly more importance to part-time work (p = 0.001), whereas SUB residents attached more importance to getting a leading position as a main goal (p = 0.0001). CONCLUSIONS There are considerable differences between GIM and SUB residents regarding career motivation and their views on working conditions and work-life balance. It is essential to understand the factors that motivate or deter the next generation in order to ensure the attractiveness of the profession of GIM.